KUALITAS AIR DAN DAMPAK SOSIAL EKONOMI MATA AIR SIKUMBANG SEBAGAI SUMBER AIR BERSIH BAGI MASYARAKAT DESA PULAU SARAK KABUPATEN KAMPAR - Helvitri Helvitri; Syafruddin Nasution; Sofia Anita (Berkala Perikanan Terubuk, 2020)
Water from the Sikumbang spring has been used by Pulau Sarak Village community to fulfill their daily needs of water, especially for cooking and drinking. Even people used to drink the water directly without boiling it. There were physical, chemical and microbiological parameters measured.  Results shown that the location of the spring was in good condition. The spring was protected with covered concrete tank.Around the spring there were many types of wooden trees such as Hevea brasilensis, Calamus ornatus, Arthocarpus integra, Myristica sp.,Eurycoma longifolia, Tetrastigma sp., Beccauera sp.,and  Nephrolepis sp. There were also many types of animals such as Tupai gils, Sus scrofa, Varanus salvator, Panthera tigris, Macaca nemestrina, hypsiscopus, Pycnonotus aurigaster, Treron Capelleiongifolia, Tetrastigma sp., Beccauera sp., Nephrolepis present in that area. In general, the condition of the area around the spring was good. Results on water quality analysis shown that the water in general is good, with Total Coliform 3/100, pH 5, BOD 1.65 mg/L, COD 7.675 mg/L, Fe 0.059 mg/L, Cd 0.0022, Pb 0.0035, Cu 0.01, Nitrat 0.065, Nitrit 0.051, Fosfat 0.0665, temperature 30.24OC, TSS 28.5 mg/L, TDS 99.5 mg/L, parameters measured.  However, the pH was relatively low (5) and total Colie was present (3/ 100 ml). As the drinking water should have neutral pH and zero total colie, the Sikumbang water need to be boiled before being consumed. In the Pulau Sarak Village, there were 11 water distributors. The water from the spring was collected in big concrete tanks and then was put in 30L/jerrycan. The presence of the Sikumbang spring was also positively affect the economy of the Pulau Sarak Village inhabitants